Access to Symmetrical and Unsymmetrical Cyclobutanes via Template-Directed [2+2]-Photodimerization Reactions of Cinnamic Acids - Yagci, Bilge Banu; Munir, Badar; Zorlu, Yunus; Türkmen, Yunus Emre (Synthesis, 2023)
In this work, we have developed a general and broadly applicable template-directed photochemical [2+2]-cycloaddition reaction which provides access to a wide range of symmetrical and unsymmetrical cyclobutane products. The use of 1,8-dihydroxynaphthalene as a covalent template paved the way for successful and highly selective photochemical homodimerization and heterodimerization reactions in the solid state between cinnamic acid derivatives. Notably, the method works equally well with aryl- and heteroaryl-containing substrates leading to the formation of β-truxinic acid analogues as single diastereomers and in high yields (up to 99%).
Keywords: cinnamic acids; [2+2] cycloaddition; cyclobutanes; heterodimerization; photochemistry; template-directed synthesis; truxinic acids